2020
DOI: 10.18502/ijph.v49i5.3203
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy in Iranian Women: A Systematic Review and Meta-Analysis

Abstract: Background: Inadequate health literacy (HL) is associated with poorer health outcomes and worse health care. Up to one-half of Iranian women have difficulty in interpreting medical information, and national HL assessment has been limited in Iran. We have undertaken a systematic review of the literature and used a metaanalysis to examine the situation of HL status in Iranian women, and determine the relationship between HL and self-efficacy, and self-care behaviors. Methods: Six databases (PubMed, Web of Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…This finding may not be restricted to migrants: a current scoping review found only 12 studies on men’s health literacy worldwide 102. In contrast to that, another systematic review focusing on health literacy in women living in Iran revealed 34 studies 103. Furthermore, even within the studies included in the meta-analysis, the number of female participants (n=8012) far exceeded that of men (n=5380).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding may not be restricted to migrants: a current scoping review found only 12 studies on men’s health literacy worldwide 102. In contrast to that, another systematic review focusing on health literacy in women living in Iran revealed 34 studies 103. Furthermore, even within the studies included in the meta-analysis, the number of female participants (n=8012) far exceeded that of men (n=5380).…”
Section: Discussionmentioning
confidence: 91%
“… 102 In contrast to that, another systematic review focusing on health literacy in women living in Iran revealed 34 studies. 103 Furthermore, even within the studies included in the meta-analysis, the number of female participants (n=8012) far exceeded that of men (n=5380). Thus, in the context of male migration, gender might be a blind spot in health literacy research.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the sense of self-efficacy plays a role in how individuals manage actual situations. There are indications that the level of self-efficacy and high-risk behaviors are negatively interrelated [ 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adequate mothers’ ability to understand, evaluate, and use health information is essential during pregnancy, particularly regarding risky health behavior and preventive behaviors [ 8 , 13 , 17 ]. However, despite the growing recognition of the crucial role of health literacy in individuals and community settings, there are limited studies on the health literacy level in pregnant women and its association with health behavior and health outcomes during pregnancy [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some scholars had conducted systematic reviews of MHL, there were some limitations: Kilfoyle et al (2016) conducted a systematic review and summarized the relationship between health literacy and women's reproductive health knowledge, behaviours, and outcomes in high‐income countries, without reporting the theoretical framework used in the review. Charoghchian et al (2020) conducted a systematic review and determined the HL's impact on lifestyle intervention in postpartum women but did not consider the early parenting behaviours. Zibellini et al (2021) conducted a systematic review of randomized controlled trials and few studies included in this review offered clear definitions of HL and only retrieved two instruments.…”
Section: Introductionmentioning
confidence: 99%